Efektivitas Cognitive Behavior Therapy (CBT) Dalam Penanganan Pasien Skizofrenia Paranoid - Shifatul 'Ulyah; IGAA Noviekayati (Jurnal Studia Insania, 2022)
The aim of this study was to intervene in one paranoid schizophrenic patient. Researchers provide interventions in the form of Cognitive Behavior Therapy (CBT) with the aim of being able to change negative, irrational and distorted belief systems to be positive and rational so that they gradually have somatic reactions and behaviors that are healthier and normal .. The research methods used in research is a qualitative case study research. The case study design used in this study is a case study with a single level analysis. Subjects in this study were 27-year-old male diagnosed with paranoid schizophrenia. The results of this study indicate that Cognitive Behavior Therapy (CBT) is effectively used as a therapeutic tool in the formation of negative subject thought patterns and behavior to be more positive and can develop the subject's potential